Working sector and participation relationship: Rukun Tetangga activities in Northern State of Malaysia / Ahmad Zaharuddin Sani Ahmad Sabri...[et al.] - Ahmad Sabri, Ahmad Zaharuddin Sani; Mohammad, Noor Afifah; Abu, Roziya (Universiti Teknologi MARA, Kedah, 2016)
Rukun Tetangga Scheme (RTS) was introduced in 1975 following the enforcement of Necessary Rules (Rukun Tetangga) 1975. The main purpose of these rules is to safeguard the people in their residential area due to safety problems and issues arising. The instrument used for this research is done through the quantitative findings by using questionnaires that have been distributed around communities of Rukun Tetangga in the Nothern State in Malaysia. From 2,000 questionnaires that had been distributed, 1866 respondents have responded. The research data had been analysed by using the description statistics. From numerous elements in the questionnaires, this paper will covered two chosen elements from the research questionnaires which are the communities working sector and their participation in Rukun Tetangga. The instrument used is IBM SPSS 20.0 to analyse these research findings. Therefore, this research shows that working sector are one of the factors that influence participation of communities in Rukun Tetangga activities. In order to ensure the continuous of participation in RT activities, they should always have a good time management and knowledge about the activities